The Dead Sea scrolls a full history - Fields, Weston W. (Leiden : Boston : Brill, 2009)
"Since 1998, W. W. Fields has investigated how the Dead Sea Scrolls were discovered, acquired,and edited. This first volume of his "Full History" covers the years 1947-1960. It is rich in detail and discloses the history of the Dead Sea Scrolls based on interviews with the first generation of Dead Sea Scrolls scholars and other people involved in their discovery and publication. In the course of his interviews, Fields has unearthed a wealth of archival material, including diaries and letters previously unknown to the public, which add significant source material to his account. The book is thoroughly illustrated with historic photographs, many in color, illuminating the discovery and editing of the scrolls." -- Publisher summary.
First discoveries at Qumran -- The mysteries of cave I -- Discoveries at Wadi Murabba'at -- The bountiful year -- More acquisition and decipherment -- The cave 4 team -- The St. Mark's scrolls return -- The most productive year -- Cave 4 work continues but is stopped by the Suez Crisis -- Regrouping after Suez -- The last cave 4 scrolls -- The museum is on the brink -- A ray of hope for the museum
"A summary and preview of this book was published ... as The Dead Sea Scrolls, a Short History"--Vol. 1, p. [5].
Includes bibliographical references and index.
Description based on print version record.
Keywords: Dead Sea scrolls -- History; Dead Sea scrolls -- Publication and distribution; Scholars -- Interviews; RELIGION / Judaism / Sacred Writings; Electronic books